The effects of the acute administration of low-dosage ethanol on the phasic neurochemical oscillations of the basal ganglia - Noori, Hamid Reza (Mathematical medicine and biology, 2012)
The effects of the acute ethanol consumption on the brain's neurochemistry are largely studied at the synaptic level. Here, the acute action of low dosages of ethanol, in terms of the inhibition of the glutamatergic system through antagonizing the N-methyl-D-asparate receptors, on the neurochemical oscillations along the neurocircuitry of the basal ganglia is investigated by mathematical models.